2012
DOI: 10.3357/asem.3325.2012
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Laser-Assisted In Situ Keratomileusis (LASIK) at Altitude

Abstract: LASIK eyes exposed to extreme altitudes under operational conditions, where the exposure is limited to 30 min or less, are expected to remain stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, previous military studies assessed outcomes of PRK and LASIK under simulated or controlled environments, including firing performance, flight performance, night driving, target detection and identification, as well as aspects associated with adverse or extreme conditions such as low light, high altitude or hypoxia, and G force environment. [1][2][3][11][12][13][14][15][16][17] These studies have yielded positive outcomes and generally supported the operational benefits of PRK and laser in situ keratomileusis. No U.S. military studies to date have performed similar evaluation after the SMILE procedure.…”
Section: Discussionmentioning
confidence: 94%
“…For example, previous military studies assessed outcomes of PRK and LASIK under simulated or controlled environments, including firing performance, flight performance, night driving, target detection and identification, as well as aspects associated with adverse or extreme conditions such as low light, high altitude or hypoxia, and G force environment. [1][2][3][11][12][13][14][15][16][17] These studies have yielded positive outcomes and generally supported the operational benefits of PRK and laser in situ keratomileusis. No U.S. military studies to date have performed similar evaluation after the SMILE procedure.…”
Section: Discussionmentioning
confidence: 94%
“…After its approval by the USAF in May 2007, over 2200 aircrew underwent LASIK in 2010 [ 54 ] . Studies on LASIK eyes exposed to short-term hyperbaric hypoxia revealed only minor refractive changes, as presented in Table 1 [ 55 - 58 ] .…”
Section: Resultsmentioning
confidence: 99%
“…The same is true for LASIK corneas due to the superficial nature of the surgery [ 59 ] . LASIK eyes, even when exposed to extreme altitudes under military operational conditions (exposure time ≤ 30 min), are expected to remain stable [ 55 ] . In contrast, structural changes in RK corneas result in a hyperopic shift [ 61 - 63 , 141 ] .…”
Section: Discussionmentioning
confidence: 99%